I Played 1991: The Greatest Arcade, Console and Home Computer Game Themes of 1991 (Brave New Worlds, 2014)
Description Not Provided
Street Fighter II Theme (From "Street Fighter II") (1:04), Ruins (From "Golden Axe II") (1:30), Sonic The Hedgehog Title Screen (From "Sonic the Hedgehog") (0:09), Game Over (From "Streets Of Rage") (0:06), The Legend of Zelda: A Link to the Past Theme (From "The Legend of Zelda: A Link to the Past") (0:43), Terminator 2: Judgment Day Theme (From "Terminator 2: Judgment Day") (1:51), Road Rash Theme (From "Road Rash") (2:20), Double Dragon 3: The Rosetta Stone Theme (From "Double Dragon 3: The Rosetta Stone") (1:27), Theme From Monkey Island 2: LeChuck's Revenge (From "Monkey Island 2: LeChuck's Revenge") (0:33), The Simpsons Theme (From "The Simpsons") (1:52), Ninja Gaiden 2 Theme (From "Ninja Gaiden 2") (2:24), Turrican 2 Theme (From "Turrican 2") (2:38), Dyna Blaster Theme (From "Dyna Blaster") (2:31), Elf (From "Elf") (3:01), Logical (From "Logical") (2:37), Gauntlet III Main theme (From "Gauntlet III") (2:39)